Die Existenzbedingungen der Lösung eines Gleichungssystems - Kabaila, V. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Кабайла. Условия существования решений одной системы уравнений V. Kabaila. Vienos lygčių sistemos sprendinio egzistavimo sąlygos